2015
DOI: 10.1002/pssa.201532127
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition, piezoelectric, and multiferroic properties of La(Co0.5Mn0.5)O3-modified BiFeO3-BaTiO3lead-free ceramics

Abstract: (0.75–x)BiFeO3−0.25BaTiO3−xLa(Co0.5Mn0.5)O3 + 1 mol% MnO2 lead‐free ceramics (x = 0–0.10) were synthesized by a conventional solid‐state reaction route and the effects of La(Co0.5Mn0.5)O3 on phase transition, piezoelectric, ferroelectric, and multiferroic properties of the ceramics were investigated. The ceramics can be well sintered at 960 °C for 2 h. After the addition of La(Co0.5Mn0.5)O3, the crystal structure of the ceramics is transformed from rhombohedral (space group R3c) to orthorhombic symmetry (space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 56 publications
(57 reference statements)
0
7
1
Order By: Relevance
“…Dopants in the field of piezoelectric materials are classified into three groups; donor (higher valence), acceptor (lower valence) and self‐compensated (average valence number remains the same). All the above‐mentioned dopant strategies improve the resistivity of BT‐BF ceramics as reported in the literature . Wang et al reported that Nb (donor) improves the resistivity of BT‐BF while it gives rise to a decrease in the grain size.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Dopants in the field of piezoelectric materials are classified into three groups; donor (higher valence), acceptor (lower valence) and self‐compensated (average valence number remains the same). All the above‐mentioned dopant strategies improve the resistivity of BT‐BF ceramics as reported in the literature . Wang et al reported that Nb (donor) improves the resistivity of BT‐BF while it gives rise to a decrease in the grain size.…”
Section: Introductionmentioning
confidence: 89%
“…For instance, as Yao et al reported, Mn increases the resistivity and decreases the dielectric loss of 0.8BF‐0.2BT ceramics. However, the most successful dopants are stoichiometric or self‐compensated (e.g., Cr, Co, Al, Ga, Mg 1/2 Ti 1/2 , Zn 1/2 Ti 1/2 , and Ni 1/2 Ti 1/2 ) which improve not only the resistivity of furnace cooled ceramics but also their piezoelectric properties . Nonetheless, the d 33 of furnace‐cooled doped BF‐BT compositions is typically much smaller (163 pC/N) than that of quenched samples …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8] Among the numerous lead-free piezoelectric ceramics, BaTiO 3 (BT) has gained many attentions on account of its low cost, easy processing, and good temperature stability.Whether for the lead-free or lead-based piezoelectric ceramics, an effective method to acquire high piezoelectric properties is to adjust the composition of the material to the vicinity of the phase transition boundaries. [9][10][11][12][13][14] Paraelectric to ferroelectric phase transition or two ferroelectric phase transition could be induced by the compositions, resulting in the instablility of the polarization state. Therefore, the polarization direction could be easily rotated under external stress or electric field, so that high piezoelectric properties could be achieved.…”
mentioning
confidence: 99%